2022
DOI: 10.1101/2022.01.09.475429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanics of human embryo compaction

Abstract: The shaping of the human embryo begins with compaction, during which cells come into close contact and form a tighter structure. Assisted reproductive technology (ART) studies suggest that human embryos fail compaction primarily because of defective adhesion. Based on our current understanding of animal morphogenesis, other morphogenetic engines, such as cell contractility, could be involved in shaping the human embryo. However, the molecular, cellular and physical mechanisms driving human embryo morphogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Surprisingly, C. elegans morphogenesis has received little attention, despite its wide-spread use as a model system for genetics and development. Compared to other model systems, such as mouse (Maitre et al, 2016) and human preimplantation embryos (Firmin et al, 2022), drosophila retina (Godard et al, 2020; Hayashi and Carthew, 2004), ascidians (Godard et al, 2020) or frog gastrula (David et al, 2014)), the development and lineage specification in the C. elegans embryo is very rapid. At early stages, the cell cycle lasts only 10-20 minutes and cell type is specified from the 4-cell stage onwards by a combination of asymmetric divisions, rotational movements (Singh and Pohl, 2014; Sugioka and Bowerman, 2018), as well as Wnt (Rocheleau et al) and Notch signaling (Mickey et al, 1996; Thorpe et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, C. elegans morphogenesis has received little attention, despite its wide-spread use as a model system for genetics and development. Compared to other model systems, such as mouse (Maitre et al, 2016) and human preimplantation embryos (Firmin et al, 2022), drosophila retina (Godard et al, 2020; Hayashi and Carthew, 2004), ascidians (Godard et al, 2020) or frog gastrula (David et al, 2014)), the development and lineage specification in the C. elegans embryo is very rapid. At early stages, the cell cycle lasts only 10-20 minutes and cell type is specified from the 4-cell stage onwards by a combination of asymmetric divisions, rotational movements (Singh and Pohl, 2014; Sugioka and Bowerman, 2018), as well as Wnt (Rocheleau et al) and Notch signaling (Mickey et al, 1996; Thorpe et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, in embryos with increased basal contractility and surface tension, the same ectopic activation of the PBE pathway triggers fragmentation (Fig 4 and Fig S3). Interestingly, in a recent study, we measured the surface tension of human embryos and reported tensions 5-10 times higher than for mouse embryos (Firmin et al, 2022). Thus, with unstable spindles and high contractility, human embryos cumulate two features that could synergistically promote fragmentation (Fig 5).…”
Section: Main Textmentioning
confidence: 95%
“…Maître et al. numerically simulated the mammalian blastocyst in 3D using a multimaterial mesh-based surface-tracking method ( Maître et al., 2016 ; Da et al., 2014 ; Firmin et al., 2022 ; Turlier and Maître, 2015 ). They hypothesized that compaction and internalization were due to differing contractility between cells, which they implemented using surface tension.…”
Section: Existing Models Of Blastocyst Formationmentioning
confidence: 99%